Ensino das frações no ensino fundamental: proposta de sequências didáticas - Pinheiro, Mary Jane Alcantara (2021)
Although the teaching of fractions started in elementary school, most students arrive at high school without knowing how to solve contextualized problems involving operations with rational numbers in fractional form. This research proposes to present didactic alternatives to contribute to the teaching and learning of this content with the proposal of didactic sequences to be worked in teacher training that teach the content in the initial grades of Elementary School. The diagnostic evaluation carried out with students from the 1st year of high school in public schools in the State of Espírito Santo proves the limitations of students' knowledge about fractional rational numbers and the need for didactic interventions for teaching content still in the base, in initial grades of elementary school. On the other hand, both the literature review and the documentary analysis of the curricular matrices of the Pedagogy courses offered in Grande Vitória, as well as the analysis of data from the interview with undergraduate students in pedagogy about their perception in relation to the mathematical training they receive in the course and more specifically about the teaching of Fractions demonstrate that the training proposed in the curricular organization of degrees in pedagogy is not sufficient for the adequate approach to the teaching of fractions in the initial grades with the use of diversified didactic practices and resources. In this perspective of collaboration with the mathematical education of the teacher of the initial series, the research presents as didactic sequences that present facilitated and diversified forms for the teaching of fractions material that can be proposed in workshops and continuing education courses for elementary school teachers.